KEPUASAN, MOTIVASI, KETERLIBATAN KERJA TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN KAMPUS BANGAU UNIKA MUSI CHARITAS - Maria Fransiska Sri Sulistyawati; Dewi Sri; SRI ANDAYANI (Catholic University Musi Charitas, 2018)
The purpose of this research is to examine and analyze the Effect of Job Satisfaction, Motivation, Work Involvement on Organizational Commitment in Bangau Campus Employees at Catholic University of Musi Charitas in Palembang. Research respondents were the employees as educators, namely lecturers without additional assignments and lecturers with additional (structural) assignments and employees as educational support staff at the Faculty of Science and Technology and the Faculty of Business and Accounting at Catholic University of Musi Charitas in Palembang. The results of the discussion Against Organizational Commitment In Bangau Campus Employees At Catholic University Musi Charitas of Job Satisfaction, Motivation, Work Involvement. Analysis techniques uses quantitative and qualitative analysis. The research method is a case study. Sampling technique is convinience.. The results of the study are expected to be beneficial to improve job for improving job satisfaction, motivation, involvement and organizational commitment. Furthermore, the results may be beneficial as inputs for various policies needed for the progress and continuity of organizational life. Finally, for further research, this study may be used as the information materials by combining other variables outside the variables that have been studied.